Martin Silicates as Versatile Radical Precursors in Photoredox/ Nickel Dual Catalysis - Wiethoff, Maxim-Aleksa; Abdellaoui, Mehdi; Deis, Thomas; Corcé, Vincent; Lemière, Gilles; Ollivier, Cyril; Fensterbank, Louis (Synlett, 2023)
A cross-coupling methodology is described based on the nickel-catalyzed connection of an aryl moiety to an alkyl radical generated by photoinduced single-electron oxidation of a silicate formed from a Martin spirosilane. Complementary to the other anionic radical precursors in photoredox catalysis, Martin silicates permit access to highly reactive alkyl radicals directly engageable in smooth C(sp2)–C(sp3) bond-formation reactions.
Keywords: dual catalysis; photoredox catalysis; nickel catalysis; cross-coupling; Martin silicates; C–C bond formation